Study on the Implementation of Good Manufacturing Practices and Sanitation Standard Operating Procedures in Frozen Tuna Products at a Fish Processing Unit - Edi Rukyanto; Rr. Juni Triastuti; Akhmad Taufiq Mukti (Universitas Islam Lamongan, 2024)
Tuna is one of the most important fishery commodities for export. Commodities that can be exported must first have certificates of feasibility for class A and class B fish processing. Class A fish processing feasibility certificates are used for export at the international level while those in class B are used for exports at the Asian level. The initial certifications that need to be met are Good Manufacturing Practices (GMP) and Sanitation Standard Operation Procedure (SSOP). The aims of this study was to determine the profile of the Fish Processing Unit (UPI) with processing feasibility certification with A and B qualifications for tuna commodities through the application of Good Manufacturing Practices (GMP) and Sanitation Standard Operation Procedure (SSOP) and deviations that occur in Fish Processing Units (UPI). The method used in this study is a quantitative descriptive observational design. The results show that many of the results of supervision of feasibility certificates for processing medium-large scale fish processing units in East Java still have a B qualification. From the results that tuna is still widely exported at the Asian level.